ANALISIS PENERAPAN TEKNOLOGI INFORMASI DALAM PENINGKATAN KINERJA KARYAWAN DIVISI SUMBERDAYA MANUSIA - Gonan Sumadi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2017)
In analyzing the influence of the application of information technology in the form of the use of special applications and software assistance is done regression and correlation approach to obtain the level of significance of the hypothesis used. In this study the variables used are the application of application and software as independent variables and performance of human resource division as the dependent variable. By using 15 trading companies as obejek research and 75 karyewan human resources division conducted analysis to obtain information magnitude influence of each variable. From the measurement and analysis, it is known that the application and software applications in supporting the performance of the human resources division showed a significant influence both simultaneously.From the measurement and analysis results it is known that the application and software sourcing in supporting the performance of human resources division showed significant influence either simultaneously (simultaneously) or partially.Therefore, it is suggested that the need for training and coaching for employees in utilizing) or partially. Therefore it is recommended that training and coaching for employees in utilizing information technology and supporting equipment improvements.